Cyclicality of human-centered development of Ukraine in the system of principles of state strategic planning - Stolyarov V., Shinkaryuk О., Stolyarova V., Vorobey S. (Економічний вісник Донбасу, 2024)
The article considers the conceptual provisions of increasing the social responsibility of central bodies and legislative and executive authorities of Ukraine for the preparation, adoption and implementation of national decisions. Examples of violation of the established deadlines for bringing decisions to regional and local authorities are given. Consideration of the principles of state and strategic planning of draft laws of 2011 and 2017, as system-forming foundations of statehood, ensured the identification of the root causes of the violation of the 1996 Constitution as a united, sovereign and independent state. Long-term management errors and tactical blunders in statehood were identified. The main reason for the cyclical nature of human development in the regions is recognized as the inability of central authorities to strategically manage Ukrainian society. The need for the formation of the Planning Code of Ukraine as a complex of strategic and tactical national decisions and the basis for increasing the social responsibility of authorities of different levels is proven. The construction of a new economy of a renewed state is focused on ensuring the centrality of planning decisions of state entities in the course of the purposeful implementation of a single nationwide socio-economic policy.